ChemInform Abstract: The Stereochemistry of Two Monoterpenoid Diastereomers from Ferula dissecta. Issue 48 (2nd December 2014) - Wang, Zhi‐Qiang; Huang, Chao; Huang, Jian; Han, Hong‐Ying; Li, Guo‐Yu; Wang, Jin‐Hui; Sun, Tie‐Min
Abstract The title compounds show significant growth inhibitory activities against cervical cancer HeLa cells.